Assessment of Complications Associated with Various Anesthetic Techniques in Patients Undergoing Hip Replacement Surgeries: A Retrospective Study - Tyagi, Vivek; Chand, Pramod; Singh, Navab (Academia Anesthesiologica International, 2019)
Background: Hip fracture in the elderly is a very common fracture, which mainly requires surgical treatment. Hence; we planned the present study to assess various complications associated with various anesthetic techniques in patients undergoing hip replacement surgeries. Subjects and Methods: Analysis of data files of a total of 160 patients was done. Retrieval of complete demographic and clinical data of all the subjects included in the present study was done. Recording of following parameter was done: Form of anaesthetics technique, Surgical procedure duration, and Fluid type and amount administered. Complication of the results was done by SPSS software. Results: Most commonly observed complications observed in the present study were hypotension, bleeding, embolism and cardiac arrest. Non- significant results were obtained while comparing the occurrence of complications among different study groups. Conclusion: Various types of anaesthetics techniques can be used with equal effectiveness among patients undergoing Hip replacement surgery.